Salal (Gaultheria shallon) and aronia (Aronia melanocarpa) fruits from Orkney: Phenolic content, composition and effect of wine-making. (15th August 2016) - McDougall, G.J.; Austin, C.; Van Schayk, E.; Martin, P.
Highlights: The polyphenolic composition of salal fruits is described for the first time. Salal fruit wine retains a deeper red coloration than those made from aronia fruits. Deeper red coloration may result from stability of specific anthocyanins in salal. Wines contain characteristic degradation products from anthocyanins and flavonols. Mixed salal and aronia wine differs markedly in composition from single fruit wines. Abstract: The polyphenol content and composition of salal and aronia fruits from plants established in Orkney was examined. The composition of the salal fruits has not previously been recorded, and they contained anthocyanins, flavonols, hydroxycinnamates and proanthocyanins. The aronia fruits contained anthocyanins, hydroxycinnamates and flavonols as previously described. Although salal fruits had half the anthocyanin content of aronia fruits, salal wine had higher anthocyanin content, probably due to the relative stability of diglycoside pentose anthocyanins. The wines contained components suggestive of anthocyanin and flavonol degradation, but there was no consistent pattern to stability within phenolic sub-classes. Indeed, the wine made from equal amounts of salal and aronia fruits had patterns of recovery of individual phenolic components which could not be predicted from recoveries in wines from single fruits. This strongly suggests that stability of individual phenolic constituents during wine-making is influenced by the presence and relative stability of other components.